Analysis of the Effect of Novel Coronavirus 2019 (Covid-19) Spreading Toward Sharia Stock Market in Indonesia - Rachmat Sunjoto, Arie; Umam, Khoirul; Huda, Miftahul; Maisaroh Aribah, Shafira (TSAQAFAH, 2024)
The purpose of this research is to identify and analyze the influence of the spread of Novel Coronavirus 2019 (Covid-19), the policies of Indonesian Government during pandemic (i.e. work from home, large-scale social restrictions (PSBB) and community activities restriction enforcement (PPKM), the movement of FTSE 100 and Nasdaq Composite indexes on Islamic stock market in Indonesia (represented by the Indonesian Sharia Stock Index). This study utilizes the Vector Error Correction Model (VECM), Impulse Response Function (IRF), and Forecast Error Correction Model (FEVD) approach, with the range data from September 2019 to November 2022.  The results of this research indicates that the VECM test showed that Covid-19 case in Indonesia and the movement of FTSE 100 had a significant positive effect on ISSI in the long term. Meanwhile, in the short term, Covid-19 case in Indonesia and government policies have had a significant negative effect on ISSI. In the IRF test, this shows that the Covid-19 case in Indonesia and government policies during pandemic have had a significant negative effect on ISSI. Conversely, the movement of the FTSE 100 and Nasdaq Composite Index has a significant positive effect on ISSI. In the FEVD test, it can be seen that the biggest contribution to ISSI shock movement was the shock itself of 85.24% and was followed by government policies, the Covid-19 case, FTSE 100 and Nasdaq. This investigation use three variables in order to search the effect of these factors on the movement of sharia stock market in Indonesia. The stock market represented by Indonesian Sharia Stock Index (ISSI).